Effectiveness of Ecotourism Sector-Based Economic Strengthening Models for Local Community Entrepreneurial Competencies - WILDAN, WILDAN; SUKARDI, SUKARDI (Journal of Environmental Management and Tourism; Vol 11 No 2 (2020): JEMT Volume Xi Issue 2(42) Spring 2020DO - 10.14505//jemt.v11.2(42).09, 2020)
The economic injustice and the imbalance of natural resources resulting from tourism exploitation requires other alternatives in its management, such as ecotourism. However, this demand can only be realized if from the beginning, the community has been prepared to be a major player in the ecotourism management. The present study aimed at discussing a model of economic empowerment based on leading ecotourism sectors towards the competency of local community entrepreneurs. This study uses a pre-trial procedure by designing a group pretest-posttest. Samples were drawn from the jewelry, cultivation, culinary and souvenir ecotourism product business groups chosen purposively. The data were collected with project-based assessment and the analyzed comparatively. The new model consists of 5 (five) main components, namely: objectives, targets, materials, procedures, and evaluations. The products consist of: community economic improvement guidelines, ecotourism product development modules (crafts, culinary, aquaculture, and souvenirs), business development and marketing modules, and project production guides. The experiment shows that the ecotourism sector-based economic development model has proven to be effective in the formation of local community entrepreneurship competencies in producing ecotourism products. The implication is that it needs support from the policies makers and the importance of the extension of sustainable economy theory in tourism sector in the Indonesian context.